OPTIMIZATION OF THE EVAQUATIVITY PROCESS OF ENVIRONMENTS FOR AIR-WORTHINESS SANITARY TRANSPORT AFTER THE DETERMINED AIRPLANE LOCATION ON THE WATER SURFACE - Стратонов, В. М.; Кукалець, Л. М.; Марченко, В. М.; Мельник O. В. (Science-based technologies, 2019)
This article examines a current problem of passengers’ and aircraft crew members’ survival assurance while performing ditching. In particular, the situation is considered when victims will be transported by the air sanitary transport - helicopter. Defined that the search and rescue forces used at this time the Mi-8MT helicopters, which have a cruising speed of 225-230 kph, and the capacity for accommodating 12 seriously injured persons (with accompanying personnel), or 24 passengers (lightly injured). Working on the problem, it is carried out the analysis of bodies and forces which bear responsibility for the search and rescue operations performance in the Black Sea area; standby forces, their readiness condition, and the mission of search and rescue facilities are determined. To develop an adequate model of evacuation process optimization, we have analyzed legislatively established categories of injured and a probable distribution of injured according to types and severity of injuries at air crashes. Based on analysis of the statistics of aviation accidents and the results of the scientists for calculations we selected the correlation: from the total number of people on board the aircraft - 90% will be injured, 20% of which will belong to the first category (red), 30% - to the second category (yellow), and 50% to the third category (green). It was also taken into account the distribution of medical institutions on categories according to the volume of services to be provided by. We have proposed three categories of injured (sorting category): " SC I" " SC ІІ", " SC ІІІ", and two categories of medical institutions (Multiprofile Intensive Care Hospitals) - "MICH-ІІ" and " MICH -І&quot. A mathematical problem statement about the optimization of evacuation has been formulated according to the principles of problems of integer programming and considered sorting categories of injured, hospitals, and indicators of fatalities at transportation. We were guided by statistics to determine the probability of death during the transportation of injured people. The article reflected results will form the ditching optimum place choice method.